The published trend of studies on COVID-19 and dietary supplements: Bibliometric analysis - Hu, Wenzhong; Xu, Yun (Frontiers in Immunology, 2022)
(1)Background: There is no guidance on dietary supplements for the prevention or treatment of COVID-19. Therefore, we want to analyze and discuss the above puzzles by bibliometric analysis; (2) Methods: On 3 September 2022, we conducted a search of all relevant literature retrieved from the WOS core collection database from 2019 to 2022. CiteSpace software is used to build the visual co-occurrence network; (3) Results: In the study of "COVID-19 and Dietary Supplements", the total of 170 authors published 855 articles in 451 journals. Several distinct core author groups were formed by Wang, Grant, Singh, Zhu, and other authors with numerous publications. The majority of the publications came from the Shahid Beheshti University of Medical Sciences. The United States of America had the highest number of publications. By analyzing keyword clusters, we found that the research focus was dietary supplements (vitamin D, vitamin K, vitamin C), mechanisms (ferritin, specialized pro-resolving mediators (SPMs), oxidative stress), research methods (clinical trials), and the prevention and treatment strategies (lockdown) of COVID-19; (4) Conclusions: vitamin D is the mainstream dietary supplement for COVID-19. There are still numerous controversies that deserve further discussion. Such as whether the use of vitamin D or TCM offers benefits, and whether the addition of dietary supplements during the lockdown measures can help prevent COVID-19 infection.